1999
DOI: 10.1046/j.1469-8137.1999.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of 32P between interacting mycelia of a wood‐decomposing fungus and ectomycorrhizal fungi in microcosm systems

Abstract: Interactions between saprotrophic and ectomycorrhizal fungi have been largely ignored, although their mycelia often share the same microsites. The mycelial systems show general similarity to each other and, although the enzymatic potential of the saprotrophic fungi is generally considered to be higher, the importance of organic nutrient sources to ectomycorrhizal fungi is now widely accepted. In the experiments described here, nutritional interactions involving transfer of elements from one mycelium to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 42 publications
4
110
2
Order By: Relevance
“…In addition, root disruption may have relaxed mycorrhizal interference competition, allowing free-living saprotrophs to increase in abundance. This field-based finding is in accordance with previous observations of mycorrhizal interference competition in laboratory microcosms (Lindahl et al, 1999(Lindahl et al, , 2001(Lindahl et al, , 2002Werner et al, 2002). The relative importance of reduced mycorrhizal interference and substrate enrichment is, however, difficult to establish.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, root disruption may have relaxed mycorrhizal interference competition, allowing free-living saprotrophs to increase in abundance. This field-based finding is in accordance with previous observations of mycorrhizal interference competition in laboratory microcosms (Lindahl et al, 1999(Lindahl et al, , 2001(Lindahl et al, , 2002Werner et al, 2002). The relative importance of reduced mycorrhizal interference and substrate enrichment is, however, difficult to establish.…”
Section: Discussionsupporting
confidence: 92%
“…In the organic humus layers of coniferous forests, ectomycorrhizal species have been found to dominate fungal communities (O'Brien et al, 2005;Lindahl et al, 2007), and in laboratory microcosms, ectomycorrhizal fungi have been found to compete successfully with saprotrophs for soil space and nutrients (Lindahl et al, 1999(Lindahl et al, , 2001(Lindahl et al, , 2002Werner et al, 2002). Being supported by carbohydrates from their host plants rather than depending on energy from organic matter, mycorrhizal fungi may exclude saprotrophs from energy-depleted substrates, to monopolise nutrients for themselves and their hosts (Lindahl et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…From these different results or observations, it seems obvious that during Tuber sporophore differentiation, a direct transfer of hexose exists between the host and the fungus via ectomycorrhizal structures, and an indirect transfer of carbon from dead host cells or dead mycorrhizae or dead roots or exfoliating root bark via free hyphae displaying saprotrophic abilities. Nevertheless, according to Lindahl et al (1999) and Leake (2001), ectomycorrhizal fungi do not need to produce costly ligninases to acquire nutrients from dead organic matter. Rather than direct nutrient capture, ectomycorrhizal fungi may obtain nutrients via absorption of small organic molecules exogenously decomposed by saprotrophic fungi.…”
Section: Sampling Datementioning
confidence: 99%
“…In addition, the digestion (predation) of bacteria by protozoa (predators) may release nutrients (N), and mycorrhizal symbiosis increases the transfer of the mobilized N (amino acids and ammonium) and P (orthophosphate) to the host plant through the microbial loop (Koller et al 2013). Mycorrhizal fungi may transfer nutrients; that is, N from dead nematodes (Perez-Moreno and Read 2001) and P from saprotrophic fungi (Lindahl et al 1999). Thus, high species diversity may decrease the limitations of residue decomposition and increase the rates of nutrient release under both favorable and unfavorable conditions (Loeau et al 2001).…”
Section: Ecosystem Fertility: a New Paradigm For Nutrient Availabilitymentioning
confidence: 99%